Practice makes perfect: The development of a medical student-led crowdsourced question bank for self-study in undergraduate medical education - Corrado, Mario; McNeely, Carlyn; Lefebvre, Isabelle; Raichura, Rikesh; Bogie, Bryce JM; Wood, Timothy J (Canadian Medical Education Journal / Revue canadienne de l'éducation médicale)

(untitled) (Canadian Medical Education Journal, 2024)
Implication StatementThe development of multiple-choice questions (MCQs) for undergraduate medical education study purposes is resource intensive. Commercially available question banks are typically expensive, only available in English, and may not be aligned with medical school learning objectives. Here, we introduce The Ottawa Question Bank: a student-led, bilingual study resource curated to a Canadian undergraduate medicine curriculum (www.theottawaquestionbank.ca). In total, 205 medical students wrote and edited 4438 original MCQs linked to objectives from the University of Ottawa undergraduate medical education curriculum. The project has received positive feedback from both developers and users. Our experience suggests that involving medical students in MCQ development is feasible and can result in the rapid creation of a low-cost, high-quality study resource curated to a program’s learning objectives. The platform outlined here can be used as a model for other medical schools and professional degree programs to develop their own question banks, including pharmacy, dentistry, nursing, and physiotherapy. Interested programs are encouraged to contact our team for collaborative opportunities.